2020
DOI: 10.1080/09544828.2020.1839743
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the link between uncertainty and project activities in new product development

Abstract: Uncertainty is central to engineering design and New Product Development (NPD). While there has been substantial focus on dealing with uncertainty in technical systems and design information, how engineering designers react to and manage uncertainty is also critical to performance. However, an important gap remains in understanding what activities NPD teams engage in based on the specific uncertainty types they face. This gap is investigated via a conceptual framework detailing four uncertainty types (technica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 62 publications
1
7
0
Order By: Relevance
“…However, a multi‐industry study found that PEU was a strong determinant of KS, particularly explicit KS behavior (Gurbuz & Araci, 2012). Importantly, our study found multilayered evidence that uncertainty type appears to influence KS, similar to the findings in Lasso et al (2020). The fact that our exploratory approach considers the multidimensionality and differential effects of two disaggregated components (state and RU) on KS subprocesses (donating and collecting) may explain the variance between our results and those of previous studies.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…However, a multi‐industry study found that PEU was a strong determinant of KS, particularly explicit KS behavior (Gurbuz & Araci, 2012). Importantly, our study found multilayered evidence that uncertainty type appears to influence KS, similar to the findings in Lasso et al (2020). The fact that our exploratory approach considers the multidimensionality and differential effects of two disaggregated components (state and RU) on KS subprocesses (donating and collecting) may explain the variance between our results and those of previous studies.…”
Section: Discussionsupporting
confidence: 90%
“…The model is built around the integrative framework of contingency theory and the functional model of interpretation to explain the multidimensionality of and relationships between perceived environmental uncertainty (PEU) types and KS subprocesses. Examining the dimensionality of uncertainty as a KM enabler (external contingent factor) and knowledge-donating (KD) and knowledge-collecting (KC) as KM processes (internal contingent indicator) (Sahibzada et al, 2021) is a more reflective and knowledge-driven way of dealing with PEU, since the relationship between uncertainty dimensions and KM processes remains unclear (Lasso et al, 2020). Studies indicate that PEU appears to drive the enactment of KS mechanisms and activities (Hsu & Wang, 2008).…”
mentioning
confidence: 99%
“…Recent studies in the NPD context have proposed that technical uncertainty requires capabilities for physical representation (e.g. drawings, prototyping) and integration (Lasso et al. , 2020).…”
Section: Discussionmentioning
confidence: 99%
“…The impact of conceptual design is substantial since a large number of ideas are generated during this process, which is considered to facilitate the achievement of a desirable design [28]. As the conceptual design process converts the design problem at an early stage into a transparent representation of design solutions, the uncertainty and unknown are reduced [35]. With the aim of reducing the uncertainty and the unknown, which lies in the design problem, decomposition of the problem and investigation of potential design solutions are typically conducted before generating a final concept [12].…”
Section: Aesthetic Information In Conceptual Designmentioning
confidence: 99%